Thermodynamic Insights by Microscale Thermophoresis into Translesion DNA Synthesis Catalyzed by DNA Polymerases Across a Lesion of Antitumor Platinum-Acridine Complex - Hreusova, Monika; Novakova, Olga; Brabec, Viktor (International journal of molecular sciences, 2020)
Translesion synthesis (TLS) through DNA adducts of antitumor platinum complexes has been an interesting aspect of DNA synthesis in cells treated with these metal-based drugs because of its correlation to drug sensitivity. We utilized model systems employing a DNA lesion derived from a site-specific monofunctional adduct formed by antitumor [PtCl(en)(L)](NO3)2 (complex AMD, en = ethane-1,2-diamine, L = N-[2-(acridin-9-ylamino)ethyl]-N-methylpropionamidine) at a unique G residue. The catalytic efficiency of TLS DNA polymerases, which differ in their processivity and fidelity for the insertion of correct dCTP, with respect to the other incorrect nucleotides, opposite the adduct of AMD, was investigated. For a deeper understanding of the factors that control the bypass of the site-specific adducts of AMD catalyzed by DNA polymerases, we also used microscale thermophoresis (MST) to measure the thermodynamic changes associated with TLS across a single, site-specific adduct formed in DNA by AMD. The relative catalytic efficiency of the investigated DNA polymerases for the insertion of correct dCTP, with respect to the other incorrect nucleotides, opposite the AMD adduct, was reduced. Nevertheless, incorporation of the correct C opposite the G modified by AMD of the template strand was promoted by an increasing thermodynamic stability of the resulting duplex. The reduced relative efficiency of the investigated DNA polymerases may be a consequence of the DNA intercalation of the acridine moiety of AMD and the size of the adduct. The products of the bypass of this monofunctional lesion produced by AMD and DNA polymerases also resulted from the misincorporation of dNTPs opposite the platinated G residues. The MST analysis suggested that thermodynamic factors may contribute to the forces that governed enhanced incorporation of the incorrect dNTPs by DNA polymerases.
Keywords: termodynamika; Acridines; antitumor; katalýza; nukleotidy; guanin; Guanine; akridiny; DNA-Directed DNA Polymerase; DNA; DNA Replication; replikace DNA; DNA Adducts; Catalysis; tepelná difuze; DNA polymerases; Thermodynamics; translesion DNA synthesis; biokatalýza; oprava DNA; Biocatalysis; Thermal Diffusion; platinum-acridine; DNA-dependentní DNA-polymerasy; microscale thermophoresis; DNA Repair; adukty DNA; Nucleotides; Platinum Compounds; sloučeniny platiny